1998
DOI: 10.1007/s002239900505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cytotoxic Effects of Bisphosphonates In Vitro and In Vivo

Abstract: We compared the cytotoxic effects of alendronate (ALN) and incadronate (YM175) on isolated rabbit osteoclasts in vitro and on rats in vivo. In the in vitro experiment, each bisphosphonate was added to the culture of isolated osteoclasts at the final concentration of 3 x 10(-5), 3 x 10(-4), or 3 x 10(-3) M, and the amount of creatine phosphokinase (CPK) released into the medium was taken as an index of cytotoxicity at 5, 10, and 24 hours after the treatment. Also viability of osteoclasts, measured in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…In addition the present study shows and describes the physiologically relevant doses. This confirms the use of 1, 5, 10 and 20 mM concentrations in the current work with its analytical aim, despite of earlier studies using higher concentrations and others suggesting even lower concentrations to be effective (Breuil et al, 1998;Ito et al, 1998;Wood et al, 2002;Im et al, 2004;Suzuki et al, 2007;Journé et al, 2008). Table 2 clearly shows the distinct reactions for the different concentrations for each BP.…”
Section: Discussionsupporting
confidence: 81%
“…In addition the present study shows and describes the physiologically relevant doses. This confirms the use of 1, 5, 10 and 20 mM concentrations in the current work with its analytical aim, despite of earlier studies using higher concentrations and others suggesting even lower concentrations to be effective (Breuil et al, 1998;Ito et al, 1998;Wood et al, 2002;Im et al, 2004;Suzuki et al, 2007;Journé et al, 2008). Table 2 clearly shows the distinct reactions for the different concentrations for each BP.…”
Section: Discussionsupporting
confidence: 81%
“…(28) These in vivo observations are in contrast with in vitro data that point to bisphosphonates as inhibitors of the number of osteoclasts through decrease in osteoclast recruitment (71,72) or shortening of the osteoclast lifespan due to cytotoxicity (73) or apoptosis. (74) However, other in vitro studies showed that aminobisphosphonates such as alendronate are not cytotoxic (75) and do not alter osteoclast number. (76) These data, together with the histomorphometric findings, suggest that bisphosphonates act in vivo primarily on osteoclast activity.…”
Section: Discussionmentioning
confidence: 99%
“…As candidates, bisphosphonates such as alendronate are widely used for the treatment of a variety of bone diseases characterized by excessive bone resorption,16 including tumor-induced hypercalcemia,17 Paget’s disease,18 and osteoporosis 19. They have a strong affinity for calcium phosphate, the major mineral component of bone, and hamper osteoclastic bone resorption by inhibiting the key enzyme farnesyl pyrophosphate synthetase 20,21. Recently, the therapeutic value of bisphosphonates has also been expanded by the discoveries that alendronate is effective in the prevention of urolithiasis by inhibition of calcium stone formation,22 as well as inhibiting invasion of PC-3 prostate cancer cells by affecting the mevalonate pathway 23.…”
mentioning
confidence: 99%